Síntese de derivados da lactose e investigação de sua interação com lectina de Erythrina cristagalli por ensaio de inibição de hemaglutinação - Anna Paola Butera (2007)
Plant lectins are especially well suited as a model system to study the molecular basis of protein-carbohydrate recognition. Lectins are carbohydrate binding proteins other than immunoglobulins that display no enzymatic activity towards the recognized sugars. Lectincarbohydrate interactions play an important role on a miriad of biological processes. In this work, it is reported the synthesis of twenty one lactose derivatives. Four of them are lactosyl amides (acetamide and benzamide) and sulfonamides (methanesulfonamide and benzenesulfonamide) and eight are aromatic lactosides (benzyl, 2-phenylethyl, phenyl, 4-methoxycarbonylphenyl, 4-carboxylphenyl, 4-methoxycarbonylphenyl-2-nitrophenyl, 2-amino-4-methoxycarbonylphenylphenyl, 2-acetylamino-4-methoxycarbonylphenylphenyl lactosides). Two other series were obtained by modification of 6 and 6 positions of 4-methoxycarbonylphenyl lactoside (6-deoxy-6-iodo, -6-azido, -6-amino, -6-acetylamino, 6-deoxy-6-azido, -6-amino, -6-acetylamino, 6- e 6-deoxy). The relative affinity of the synthesized derivatives towards the lectin from seeds of Erythrina cristagalli was evaluated by hemagglutination inhibition assay. None of the synthetic derivatives were better inhibitors than lactose.